The Modernization Of Education System In Uzbekistan Is A Actual Problems In Public Policy - Umida Farxadovna Elmuratova (International Scientific and Current Research Conferences, 2021)
This article is revealed the important measures taken in the education system of Uzbekistan in the context of the pandemic. The state policy is analyzed on improving the quality of education, the introduction of innovations in this sphere. It justifies reforms aimed at shaping the system of innovative schools.